Combating LGBTphobia in Schools: Evidence from a Field Experiment in France - Stéphane Carcillo; Marie-Anne Valfort; Pedro Vergara Merino (Institute of Labor Economics (IZA), 2025)
This paper presents the first rigorous evaluation of school-based interventions aimed at reducing LGBTphobia. We focus on a classroom intervention that addresses the issue of LGBT harassment through perspective-taking and narrative exchange. Using a field experiment in France with more than 10,000 middle and high school students, we find robust evidence of strong positive effects, with variations across gender, age, and socio-economic status. We argue that changing perceptions of group norms is a key channel driving these heterogeneous effects.
Keywords: C93; J15; J16; J71; 330; LGBT; discrimination; social norms